Angiopoietin-2 promotes ER+ breast cancer cell survival in bone marrow niche. Issue 8 (August 2016) - Han, Hyun Ho; Kim, Baek Gil; Lee, Joo Hyun; Kang, Suki; Kim, Ji Eun; Cho, Nam Hoon
Abstract : In estrogen receptor-positive (ER+) breast cancer, it is recognized that metastases may develop after a long period of dormancy. Bone marrow (BM) vascular niche is where the dormant tumor cells are most likely to reside. So far, it is not fully understood why the dormant tumor cells become proliferative and eventually generate tumor. We hypothesized that therapeutic or menopause-related estrogen depletion may be the switch behind dormant ER+ tumor cell awakening in BM. We utilized an existing experimental model of BM endothelial niche that can simulate ER+ tumor cell dormancy to test our hypothesis. In results, estrogen depletion paradoxically promoted ER+ tumor cell proliferation in the BM endothelial niche, and their molecular phenotype shifted from dormant to awaken. Following estrogen depletion, the BM niche cells produced angiopoietin-2 ( ANGPT2 ), which destabilized niche endothelium by interfering ANGPT1 /Tie2 signaling, and promoted ER+ tumor cell survival under estrogen deficiency via cell surface integrin &1. Knockdown of ANGPT2 completely negated ER+ tumor cell awakening in the niche. Furthermore, ANGPT2 expression in ER+ tumor human samples was associated with increased risk of distant metastasis only in those who underwent adjuvant estrogen depletion therapy, not in those who did not undergo adjuvant therapy. In conclusion, we demonstrate that ANGPT2 signaling activated after estrogen depletion paradoxically triggers ER+ tumor cell awakening from dormancy in their BM niche, partly indirectly via endothelial Tie2 receptor and partly directly via tumor cell surface integrin &1.